Fabrication of high performance field-effect transistors and practical Schottky contacts using hydrothermal ZnO nanowires. (6th August 2015) - Opoku, Charles; Dahiya, Abhishek Singh; Oshman, Christopher; Daumont, Christophe; Cayrel, Frederic; Poulin-Vittrant, Guylaine; Alquier, Daniel; Camara, Nicolas
Abstract: The production of large quantities of single crystalline semiconducting ZnO nanowires (NWs) at low cost can offer practical solutions to realizing several novel electronic/optoelectronic and sensor applications on an industrial scale. The present work demonstrates high-density single crystalline NWs synthesized by a multiple cycle hydrothermal process at ∼100 °C. The high carrier concentration in such ZnO NWs is greatly suppressed by a simple low cost thermal annealing step in ambient air at ∼450 °C. Single ZnO NW FETs incorporating these modified NWs are characterized, revealing strong metal work function-dependent charge transport, unobtainable with as-grown hydrothermal ZnO NWs. Single ZnO NW FETs with Al as source and drain (s/d) contacts show excellent performance metrics, including low off-state currents (fA range), high on/off ratio (10 5 –10 7 ), steep subthreshold slope (<600 mV/dec) and excellent field-effect carrier mobility (5–11 cm 2 /V-s). Modified ZnO NWs with platinum s/d contacts demonstrate excellent Schottky transport characteristics, markedly different from a reference ZnO NW device with Al contacts. This included abrupt reverse bias current–voltage saturation characteristics and positive temperature coefficient (∼0.18 eV to 0.13 eV). This work is envisaged to benefit many areas of hydrothermal ZnO NW research, such as NW FETs, piezoelectric energy recovery, piezotronics and Schottky diodes.